Indescifrabilidad y comprensión radical - Chiurazzi, Gaetano (Escritura e Imagen, 2006)
The message sent through the spacecrafts Pioneer 10 and Pioneer 11 addressed to possible extraterrestrial beings, is the opportunity for a reflection on the minimal intelligibility conditions of writing. The radical comprehension – expression recalling the Quine’s “radical translation” and Davidson’s “radical interpretation” – concerns that lowest content of comprehension that constitutes the writing as such, making it something that demands to be understood even in its indecipherability. Such minimum content consists in its being a trace of an existence. This thesis is supported by re-going through the sense of the subjective turning point of modern philosophy that has placed the diagrammatic dimension of writing on a prominent position. Examples are the Fregean ideography (as “diagram of truth”) on the one hand and the psychoanalytic interpretation of dreams (as “diagram of desire”) on the other hand. This turning point comes to its level of radicalism in the Heideggerian ontological hermeneutics that indissolubly weaves together comprehension and existence to the point that is possible to establish an analogy between the existential analysis and the several grades of text decipherability as it is here suggested: the passage from the inauthentic to the authentic existence can be read as passage from the semantic (radical interpretation) to the syntactic (radical translation) and to the ontological level (radical comprehension). The radical comprehension level is the one in which the lowest content of comprehension coincides with its formal condition of possibility: in which comprehending is to comprehend an existence.